Martensitic stainless steel powder and martensitic stainless steel sintered body

JP7631880B2Active Publication Date: 2025-02-19SEIKO EPSON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021027108
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2025-02-19
Estimated Expiration
2041-02-24

Smart Images

  • Figure 0007631880000007
    Figure 0007631880000007
  • Figure 0007631880000001
    Figure 0007631880000001
  • Figure 0007631880000002
    Figure 0007631880000002
Patent Text Reader

Abstract

To provide martensitic stainless steel powder capable of producing a high density sintered compact without performing high densification treatment such as HIP treatment, and a martensitic stainless steel sintered compact having high density and excellent mechanical properties.SOLUTION: Martensitic stainless steel powder has a composition containing 0.42 mass% or more and 0.80 mass% or less of C, 12.0 mass% or more and 14.0 mass% or less of Cr, 1.2 mass% or more and 2.7 mass% or less of Nb, and the balance Fe with impurities, and has an average particle diameter of 10 μm or less. Further, it is preferable that C is contained by 0.50 mass% or more and 0.75 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a martensitic stainless steel powder and a martensitic stainless steel sintered body. [Background technology]

[0002] Patent Document 1 discloses a method for producing a sintered alloy, which includes a step of mixing and grinding a dispersed phase forming material, a main component Fe, a martensite binder phase forming powder, and a hard phase forming material to obtain a mixed powder, a step of molding the mixed powder to obtain a green compact, and a step of heating and sintering the green compact to obtain a sintered alloy. Patent Document 1 also discloses an additional step of performing HIP treatment on the green compact or the sintered alloy to reduce voids remaining in the sintered alloy. This allows for a sintered alloy with no residual voids inside, high density, and excellent wear resistance to be obtained. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-279959 Summary of the Invention [Problem to be solved by the invention]

[0004] However, martensitic stainless steel has a characteristic that it is difficult to increase the sintered density. If the sintered density is low, it affects the mechanical properties, and therefore it is difficult to sufficiently increase the reliability when the sintered alloy is applied to machine parts, etc.

[0005] In the method described in Patent Document 1, high density is achieved by performing HIP treatment. However, HIP treatment requires many steps. For this reason, there is a demand for a method for producing high density sintered alloys without performing densification treatment such as HIP treatment. [Means for solving the problem]

[0006] The martensitic stainless steel powder according to the present invention contains 0.42 mass % or more of C. 0.70% by mass or less Contains 12.0 mass% or more and 14.0 mass% or less of Cr, and contains 1.2 mass% or more and 2.7 mass% or less of Nb, The Si content is 0.65 mass% or more and 1.0 mass% or less, the Mn content is 0.71 mass% or more and 1.0 mass% or less, and the Ni content is 0.07 mass% or more and 0.60 mass% or less, The balance is Fe and Contains 0.05% by mass or less It is an impurity, In the cumulative particle size distribution on a mass basis obtained by a laser diffraction method, the particle size at which the cumulative amount is 50% from the small diameter side is defined as the average particle size D50. is 10 μm or less.

[0007] The martensitic stainless steel sintered body according to the application example of the present invention contains 0.40 mass % or more of C. 0.70% by mass or less Contains 12.0 mass% or more and 14.0 mass% or less of Cr, and contains 1.2 mass% or more and 2.7 mass% or less of Nb, The Si content is 0.65 mass% or more and 1.0 mass% or less, the Mn content is 0.71 mass% or more and 1.0 mass% or less, and the Ni content is 0.07 mass% or more and 0.60 mass% or less, The balance is Fe and Contains 0.05% by mass or less It is an impurity and is characterized by a relative density of 99.0% or more. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a process diagram showing a method for producing a martensitic stainless steel sintered body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The martensitic stainless steel powder and the martensitic stainless steel sintered body of the present invention will be described in detail below with reference to the accompanying drawings.

[0010] 1. Martensitic stainless steel powder First, the martensitic stainless steel powder according to the embodiment will be described.

[0011] In powder metallurgy, a composition containing a metal powder and a binder is molded into a desired shape, and then the molded composition is subjected to a degreasing process and a sintering process to obtain a sintered body of a desired shape. Compared to other techniques, powder metallurgy can produce sintered bodies of complex and fine shapes in a near-net shape, i.e., a shape close to the final shape.

[0012] The martensitic stainless steel powder according to the embodiment is a metal powder containing at least C, Cr, and Nb, with the balance being Fe and impurities. Specifically, the martensitic stainless steel powder according to the embodiment is a powder containing 0.42 mass% or more and 0.80 mass% or less of C, 12.0 mass% or more and 14.0 mass% or less of Cr, 1.2 mass% or more and 2.7 mass% or less of Nb, with the balance being Fe and impurities. The average particle size of this martensitic stainless steel powder is 10 μm or less.

[0013] By using such a martensitic stainless steel powder, a high-density martensitic stainless steel sintered body can be produced by powder metallurgy without densification treatment such as HIP treatment. The obtained martensitic stainless steel sintered body contains a martensite structure and has excellent mechanical properties, so that when it is applied to, for example, machine parts, it contributes to the realization of highly reliable machine parts.

[0014] The martensitic stainless steel powder according to the embodiment will be described in detail below. In the following description, the martensitic stainless steel sintered body may be simply referred to as the "sintered body."

[0015] 1.1.C (carbon) When C (carbon) is used in combination with Nb, it precipitates NbC on the surface of the metal powder particles. When carbides such as NbC precipitate on the surface of the particles, the rapid sintering of the compact is suppressed. This makes it possible to prevent the surface of the compact from being sintered unevenly due to temperature unevenness and becoming blocked. As a result, it is possible to prevent gas generated inside the compact from being trapped and to sufficiently increase the internal sintering density, resulting in a high-density sintered compact.

[0016] The C content in the martensitic stainless steel powder is 0.42% by mass or more and 0.80% by mass or less, preferably 0.50% by mass or more and 0.75% by mass or less, and more preferably 0.53% by mass or more and 0.70% by mass or less. If the C content falls below the lower limit, the amount of C relative to the amount of Nb is insufficient, and depending on the overall composition ratio, the sintering density cannot be sufficiently increased. On the other hand, if the C content exceeds the upper limit, the amount of C relative to the amount of Nb is excessive, and depending on the overall composition ratio, the sintering reaction may be inhibited and the sintering density may be reduced.

[0017] 1.2.Cr (Chromium) Cr (chromium) is an element that imparts corrosion resistance to the sintered body produced. By including Cr, the martensitic stainless steel powder realizes a sintered body that can maintain good mechanical properties for a long period of time.

[0018] The Cr content in the martensitic stainless steel powder is 12.0 mass% or more and 14.0 mass% or less, preferably 12.3 mass% or more and 13.7 mass% or less, and more preferably 12.5 mass% or more and 13.5 mass% or less. If the Cr content is below the lower limit, the corrosion resistance of the sintered body may be insufficient depending on the overall composition ratio. On the other hand, if the Cr content is above the upper limit, the sinterability of the martensitic stainless steel powder may decrease, and the sintered density may decrease depending on the overall composition ratio.

[0019] 1.3.Nb (Niobium) When used in combination with C, Nb (niobium) precipitates NbC on the surface of metal powder particles. This suppresses the rapid progress of sintering in the compact. As a result, it is possible to suppress the trapping of gas generated inside the compact and to sufficiently increase the sintering density inside the compact, ultimately resulting in a high-density sintered body.

[0020] Furthermore, the inclusion of Nb can increase the sintering initiation temperature of the martensitic stainless steel powder. This allows the martensitic stainless steel powder to remain at a high temperature at which sintering does not begin, for example, in a temperature range of 800°C or higher but below the sintering initiation temperature, for a longer period of time. As a result, even if the martensitic stainless steel powder contains substances that tend to inhibit sintering, such as oxides such as silicon oxide and chromium oxide, a reaction to reduce these substances can be efficiently carried out.

[0021] The reduction reaction can be represented by the following reaction formula: SiO 2 (s) + C(s) → SiO(g) + CO(g) Cr 2 O 3 (s) + 3C(s) → 2Cr(s) + 3CO(g)

[0022] In the above formula, (s) represents a solid and (g) represents a gas. In this example, silicon oxide, SiO 2 reacts with carbon C, changing into a substance that is easily vaporized and removed from the compact. Also, chromium oxide is reduced to metallic chromium. As a result, oxides that tend to inhibit sintering can be reduced from the compact, and the sintered body can be made denser. This reaction is likely to occur at temperatures of 800°C or higher, for example, so if the sintering start temperature can be increased, the martensitic stainless steel powder can be allowed to remain in the temperature range suitable for the reduction reaction for a longer period during the sintering process described below.

[0023] The Nb content in the martensitic stainless steel powder is 1.2% by mass or more and 2.7% by mass or less, and preferably 1.4% by mass or more and 2.5% by mass or less. If the Nb content falls below the lower limit, the amount of Nb is insufficient relative to the amount of C, and depending on the overall composition ratio, the sintering density cannot be sufficiently increased. On the other hand, if the Nb content exceeds the upper limit, the amount of Nb is excessive relative to the amount of C, and depending on the overall composition ratio, the sintering reaction may be inhibited and the sintering density may be reduced.

[0024] Furthermore, when the ratio of the C content to the Nb content is C / Nb, C / Nb is preferably 0.18 to 0.60, more preferably 0.20 to 0.50, and even more preferably 0.23 to 0.45. This allows the balance between the C content and the Nb content to be optimized. As a result, it becomes difficult for excess C or Nb to occur, and it is possible to realize a martensitic stainless steel powder that can be used to manufacture a sintered body that is highly compatible with high density and high strength.

[0025] Furthermore, when the sum of the C content and the Nb content is C+Nb, C+Nb is preferably 1.5 to 3.5, more preferably 1.7 to 3.3, and even more preferably 2.0 to 3.2. This makes it possible to prevent the absolute amount of NbC generated from being small or to prevent the generation of an excessive amount of NbC. As a result, it is possible to realize a martensitic stainless steel powder that can be used to manufacture a sintered body that is highly compatible with high density and high strength.

[0026] 1.4. Other Elements In addition to the above-mentioned elements, the martensitic stainless steel powder may contain at least one of Si, Mn and Ni, if necessary.

[0027] The Si content is preferably 1.0 mass % or less, more preferably 0.90 mass % or less, and even more preferably 0.80 mass % or less.

[0028] The Mn content is preferably 1.0 mass % or less, more preferably 0.90 mass % or less, and even more preferably 0.85 mass % or less.

[0029] The Ni content is preferably 0.60 mass % or less, more preferably 0.40 mass % or less, and even more preferably 0.30 mass % or less.

[0030] By setting the respective contents of Si, Mn, and Ni within the above ranges, it is possible to realize a martensitic stainless steel powder with excellent sinterability without unnecessarily increasing the degree of refinement of the raw materials used in the production of the martensitic stainless steel powder. In other words, by setting the respective contents of Si, Mn, and Ni within the above ranges, it is possible to obtain a martensitic stainless steel powder that can be used to produce a high-density sintered body, even if relatively inexpensive raw materials are used.

[0031] Furthermore, the martensitic stainless steel powder may contain Mo or Pb, in addition to the above-mentioned elements, if necessary.

[0032] The Mo content is preferably 0.60 mass % or less, and the Pb content is preferably 0.30 mass % or less.

[0033] 1.5.Fe (Iron) and Impurities Fe (iron) is the remainder of the elements contained in the martensitic stainless steel powder according to the embodiment, other than the above-mentioned elements. Therefore, the content of Fe is the highest in the martensitic stainless steel powder. In other words, Fe is the main component of the martensitic stainless steel powder and has a significant effect on the properties of the sintered body.

[0034] The Fe content is not particularly limited, but is preferably 50 mass % or more, and more preferably 60 mass % or more.

[0035] The martensitic stainless steel powder may contain any element other than the above elements and Fe as an impurity. The impurities may be unintentionally contained in the raw materials or may be unavoidably mixed in during the manufacturing process of the martensitic stainless steel powder. The concentration of the impurities may be lower than the content of each of the above elements, and is preferably 0.10 mass% or less, and more preferably 0.05 mass% or less. Note that Si, Mn, Ni, Mo, Pb and the impurities may be intentionally added as long as their concentrations are within the above ranges.

[0036] 1.6.Analysis method The composition of the martensitic stainless steel powder according to the embodiment has been described in detail above, and each of the above elements is identified by the following analytical method.

[0037] Examples of analytical methods include iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, iron and steel-inductively coupled plasma atomic emission spectrometry specified in JIS G 1258:2007, iron and steel-spark discharge atomic emission spectrometry specified in JIS G 1253:2002, iron and steel-fluorescent X-ray analysis specified in JIS G 1256:1997, and gravimetry, titration, and absorptiometry specified in JIS G 1211 to G 1237.

[0038] Specific examples include a solid-state optical emission spectrometer manufactured by SPECTRO, in particular a spark discharge optical emission spectrometer, model: SPECTROLAB, type: LAVMB08A, and an ICP device, CIROS120 type manufactured by Rigaku Corporation.

[0039] In particular, when identifying C (carbon) and S (sulfur), the oxygen flow combustion (high-frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211:2011 is also used. Specifically, the LECO carbon / sulfur analyzer, CS-200, can be used.

[0040] Furthermore, when specifying N (nitrogen) and O (oxygen), the method for determining nitrogen in iron and steel specified in JIS G 1228:1997 and the general method for determining oxygen in metallic materials specified in JIS Z 2613:2006 are also used. Specifically, the LECO oxygen / nitrogen analyzer, TC-300 / EF-300, can be mentioned.

[0041] 1.7. Powder characteristics The average particle size D50 of the martensitic stainless steel powder is set to 10 μm or less, preferably 1 μm to 9 μm, and more preferably 2 μm to 8 μm. Martensitic stainless steel powder with such a particle size has good sinterability and can be used to produce a high-density sintered body.

[0042] If the average particle size D50 of the martensitic stainless steel powder is below the lower limit, the powder is likely to aggregate, which may result in a decrease in sintered density. On the other hand, if the average particle size D50 of the martensitic stainless steel powder is above the upper limit, the filling property during molding may decrease, which may result in a decrease in sintered density.

[0043] The average particle size D50 of the martensitic stainless steel powder is determined as the particle size at which the cumulative amount from the small diameter side is 50% in the cumulative particle size distribution on a mass basis obtained by laser diffraction method.

[0044] In the mass-based particle size distribution of martensitic stainless steel powder obtained by laser diffraction, when the particle size at 10% cumulative from the small diameter side is defined as D10 and the particle size at 90% cumulative from the small diameter side is defined as D90, (D90-D10) / D50 is preferably about 1.0 to 2.5, more preferably about 1.2 to 2.3. (D90-D10) / D50 is an index showing the degree of spread of the particle size distribution, and by having this index in the above range, the packing property of the martensitic stainless steel powder is improved.

[0045] 2. Manufacturing method of sintered body FIG. 1 is a process diagram showing a method for producing a martensitic stainless steel sintered body.

[0046] The method for producing a martensitic stainless steel sintered body shown in Fig. 1 includes a composition preparation step S102, a molding step S104, a degreasing step S106, and a sintering step S108. Each step will be described below in order.

[0047] 2.1. Composition preparation process In the composition preparation step S102, a molding composition containing a martensitic stainless steel powder and an organic binder is obtained.

[0048] The martensitic stainless steel powder is preferably produced by atomization, more preferably by water atomization or rotary water flow atomization. The atomization method is a method for producing metal powder by colliding molten metal with a liquid or gas sprayed at high speed to pulverize and cool the molten metal. By producing the martensitic stainless steel powder by atomization, extremely fine powder can be produced efficiently.

[0049] As the organic binder, a resin that can be decomposed in a short time during degreasing and sintering is used. Examples of such resins include polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers, acrylic resins such as polymethyl methacrylate and polybutyl methacrylate, styrene resins such as polystyrene, polyesters such as polyvinyl chloride, polyvinylidene chloride, polyamide, polyethylene terephthalate and polybutylene terephthalate, polyethers, polyvinyl alcohol, polyvinylpyrrolidone, or copolymers thereof, various waxes, paraffins, higher fatty acids, higher alcohols, higher fatty acid esters, and higher fatty acid amides, and one or more of these may be used in combination. The molding composition may be in the form of, for example, a kneaded mixture, a granulated powder, or the like.

[0050] The mixing ratio of the organic binder is preferably about 0.2% by mass or more and 20.0% by mass or less, and more preferably about 0.5% by mass or more and 15.0% by mass or less, of the molding composition.

[0051] In addition to these, various additives such as plasticizers, lubricants, antioxidants, degreasing agents, surfactants, etc. may be added to the composition.

[0052] 2.2. Molding process In the molding step S104, the molding composition is molded into a desired shape, thereby obtaining a molded body.

[0053] Examples of the molding method include injection molding, compression molding, extrusion molding, and additive manufacturing. Among these, examples of the additive manufacturing method include material extrusion deposition and binder jetting.

[0054] 2.3. Degreasing process In the degreasing step S106, the green body is subjected to a degreasing treatment to obtain a degreased body.

[0055] Examples of the degreasing treatment include a method of heating the molded body to decompose the organic binder, a method of exposing the molded body to a gas that decomposes the organic binder, etc. By the degreasing treatment, all or a part of the organic binder in the molded body is removed.

[0056] When the method of heating the molded body is used, the heating conditions for the molded body will vary slightly depending on the composition and amount of the organic binder, but are preferably a temperature of 100° C. or higher and 750° C. or lower and a time of 0.1 hours or higher and 20 hours or lower, and more preferably a temperature of 150° C. or higher and 600° C. or lower and a time of 0.5 hours or higher and 15 hours or lower.

[0057] The atmosphere in which the molded body is heated is not particularly limited, and examples thereof include an inert atmosphere such as nitrogen or argon, an oxidizing atmosphere such as air, or a reduced pressure atmosphere obtained by reducing the pressure of these atmospheres.

[0058] As a method of exposing a molded body to a gas that decomposes an organic binder, for example, an acid degreasing method is used. The acid degreasing method is a method of degreasing a molded body by heating the molded body in an acid-containing atmosphere and utilizing the catalytic action of the acid. According to the acid degreasing method, the organic binder can be decomposed in a short time even at a low temperature, so that even a molded body with a large volume can be efficiently degreased.

[0059] The acid-containing atmosphere refers to an atmosphere containing an acid capable of decomposing an organic binder. Examples of such acids include nitric acid, oxalic acid, ozone, etc., and one or more of these can be used in combination. In addition, a mixed gas obtained by mixing these acids with other gases may be used. An example of the mixed gas is fuming nitric acid. The atmospheric pressure may be atmospheric pressure, reduced pressure, or pressurized.

[0060] The heating conditions for the compact in an acid-containing atmosphere can be lower in temperature or shorter in time than the heating conditions described above, which allows the amount of heat applied to the compact to be reduced, making it easier to suppress oxidation of the martensitic stainless steel powder.

[0061] 2.4.Sintering process In the sintering step S108, the degreased body is subjected to a sintering process to obtain a sintered body.

[0062] The sintering temperature varies depending on the composition ratio and particle size of the martensitic stainless steel powder, but is, for example, about 980° C. to 1330° C., and preferably about 1050° C. to 1260° C.

[0063] The sintering time is set to 0.2 hours or more and 7 hours or less, and preferably to about 1 hour or more and 6 hours or less.

[0064] The atmosphere for the sintering treatment may be, for example, a reducing atmosphere such as hydrogen, an inert atmosphere such as nitrogen or argon, or a reduced pressure atmosphere obtained by reducing the pressure of these atmospheres. The pressure of the reduced pressure atmosphere is not particularly limited as long as it is less than normal pressure (100 kPa), but is preferably 10 kPa or less, and more preferably 1 kPa or less. This allows gas remaining in the degreased body to be discharged particularly efficiently, and the final sintered body to be obtained with a high density.

[0065] The obtained sintered body may be subjected to quenching, subzero treatment, tempering, etc., as required, thereby forming a stable martensite structure.

[0066] In the quenching process, the sintered body is heated to about 950°C to about 1200°C for about 0.2 hours to about 3 hours, and then rapidly cooled. Water cooling, oil cooling, etc. are used for the rapid cooling in the quenching process.

[0067] Sub-zero treatment is a process in which the crystal structure of the retained austenite is converted to martensite by cooling without being converted to martensite by quenching. The crystal structure of the retained austenite often becomes martensite over time, but this is accompanied by a change in the volume of the sintered body, which can cause the dimensions of the sintered body to change over time. Therefore, by performing sub-zero treatment after quenching, the crystal structure of the retained austenite can be almost forcibly converted to martensite, preventing the occurrence of dimensional changes over time.

[0068] The temperature of the sub-zero treatment is set to 0° C. or lower, and the time is preferably from 0.2 to 3 hours. For cooling the sintered body, for example, dry ice, carbon dioxide gas, liquid nitrogen, etc. are used.

[0069] Tempering is a process in which the quenched sintered body is heated again at a lower temperature than that used in the quenching process, thereby making it possible to reduce the hardness of the sintered body while imparting toughness to it.

[0070] The tempering temperature is preferably about 100° C. or more and about 250° C. or less, and the tempering time is preferably about 0.3 hours or more and about 5 hours or less.

[0071] 2. Martensitic stainless steel sintered body A martensitic stainless steel sintered body according to an embodiment will be described.

[0072] The martensitic stainless steel sintered body according to the embodiment is a metal sintered body containing at least C, Cr, and Nb, with the balance being Fe and impurities. Specifically, the martensitic stainless steel sintered body is a metal sintered body containing 0.40 mass% to 0.75 mass% C, 12.0 mass% to 14.0 mass% Cr, 1.2 mass% to 2.7 mass% Nb, with the balance being Fe and impurities. The relative density of this martensitic stainless steel sintered body is 99.0% or more.

[0073] Such a martensitic stainless steel sintered body can be produced by powder metallurgy without densification treatment such as HIP treatment, and therefore a martensitic stainless steel sintered body with high density and excellent mechanical properties can be realized.

[0074] Due to the reduction reaction caused by C, the C content in the martensitic stainless steel sintered body may be lower than the C content in the martensitic stainless steel powder. Specifically, the C content in the sintered body may be 30% or more and less than 100% of the C content in the metal powder, but is preferably 60% or more and 90% or less. This makes it possible to prevent the C content from becoming too low, and suppresses deterioration of the mechanical properties of the sintered body.

[0075] In consideration of this, the C content in the sintered body is set to 0.40 mass% or more and 0.75 mass% or less as described above, but is preferably 0.45 mass% or more and 0.65 mass% or less, and more preferably 0.50 mass% or more and 0.60 mass% or less.

[0076] The above-mentioned martensitic stainless steel sintered body is used as a material for constituting all or part of, for example, transportation equipment parts such as automobile parts, bicycle parts, railway vehicle parts, ship parts, aircraft parts, and space transport vehicle parts; electronic equipment parts such as personal computer parts, mobile phone terminal parts, tablet terminal parts, and wearable terminal parts; electrical equipment parts such as refrigerators, washing machines, and air conditioners; machine parts such as machine tools and semiconductor manufacturing equipment; plant parts such as nuclear power plants, thermal power plants, hydroelectric power plants, refineries, and chemical complexes; watch parts, and decorative articles such as metal tableware, jewelry, and eyeglass frames.

[0077] The martensitic stainless steel powder and the martensitic stainless steel sintered body of the present invention have been described above based on preferred embodiments, but the present invention is not limited to these. For example, the martensitic stainless steel sintered body may be a sintered body produced from a mixed powder containing the martensitic stainless steel powder and other powders. EXAMPLES

[0078] Next, an embodiment of the present invention will be described. 3. Manufacturing of martensitic stainless steel sintered bodies 3.1 Example 1 First, a kneaded product (molding composition) containing martensitic stainless steel powder produced by water atomization and an organic binder was prepared. The metal powder used was martensitic stainless steel powder with an average particle size of 6.0 μm. The organic binder used was a mixture of polypropylene and wax. The mixing ratio of the organic binder in the kneaded product was 8 mass%.

[0079] Next, the kneaded mixture was molded in an injection molding machine to obtain a molded body, which had a rectangular shape with a length of 15 mm, a width of 15 mm, and a height of 3 mm.

[0080] Next, the green body was subjected to a degreasing treatment to obtain a degreased body, which was obtained by heating the green body at 450°C for 2 hours in a nitrogen atmosphere.

[0081] Next, the degreased body was subjected to a sintering treatment to obtain a sintered body, which was a treatment in which the degreased body was heated at 1250°C for 3 hours in an argon atmosphere. Next, the sintered body was subjected to quenching and tempering.

[0082] 3.2. Examples 2 to 11 A sintered body was obtained in the same manner as in Example 1, except that the composition ratio of the martensitic stainless steel powder was changed as shown in Tables 1 to 3.

[0083] 3.3. Comparative Examples 1 to 16 A sintered body was obtained in the same manner as in Example 1, except that the composition ratio of the martensitic stainless steel powder was changed as shown in Tables 1 to 3.

[0084] [Table 1]

[0085] [Table 2]

[0086] [Table 3]

[0087] 4. Evaluation of sintered martensitic stainless steel 4.1. Alloy composition The alloy composition of the martensitic stainless steel sintered bodies obtained in each Example and Comparative Example was analyzed. The results showed that the alloy composition was almost the same as that of the metal powder used to manufacture the sintered bodies. The C content of the sintered bodies was 70-90% of the C content of the metal powder, specifically within the range of 0.40-0.75 mass%.

[0088] 4.2. Relative Density For the martensitic stainless steel sintered bodies obtained in each of the Examples and Comparative Examples, the relative density was calculated in accordance with the method specified in JIS Z 2501: 2000. The calculation results are shown in Tables 4 to 6.

[0089] Tensile strength The tensile strength of the martensitic stainless steel sintered bodies obtained in each of the Examples and Comparative Examples was measured in accordance with the tensile test method for metallic materials specified in JIS Z 2241: 2011. The tensile test speed was 5 mm / min. The measured tensile strength was evaluated according to the following criteria.

[0090] A: The tensile strength of the sintered body is 1800 MPa or more. B: The tensile strength of the sintered body is 1600 MPa or more and less than 1800 MPa. C: The tensile strength of the sintered body is 1400 MPa or more and less than 1600 MPa. D: The tensile strength of the sintered body is 1200 MPa or more and less than 1400 MPa. E: The tensile strength of the sintered body is 1000 MPa or more and less than 1200 MPa. F: The tensile strength of the sintered body is 800 MPa or more and less than 1000 MPa. G: The tensile strength of the sintered body is less than 800 MPa. The above evaluation results are shown in Tables 4 to 6.

[0091] 4.4.Vickers hardness The martensitic stainless steel sintered bodies obtained in each of the examples and comparative examples were cut with a fine cutter. The Vickers hardness was measured at the center of the cut surface according to the Vickers hardness test method specified in JIS Z 2244:2009. The measurement load was 200 gf. The measured Vickers hardness was evaluated according to the following criteria.

[0092] A: Vickers hardness is 480 or more B: Vickers hardness is 450 or more and less than 480 C: Vickers hardness is 420 or more and less than 450 D: Vickers hardness is less than 420 The above evaluation results are shown in Tables 4 to 6.

[0093] 4.5. Oxygen content The oxygen content of the martensitic stainless steel sintered bodies obtained in each of the Examples and Comparative Examples was measured. For the measurement, an oxygen / nitrogen analyzer, TC-300 / EF-300, manufactured by LECO Corporation, was used. The measured oxygen content was evaluated against the following evaluation criteria.

[0094] A: The oxygen content is less than 0.010% by mass. B: The oxygen content is 0.010% by mass or more and less than 0.030% by mass. C: The oxygen content is 0.030% by mass or more and less than 0.050% by mass. D: The oxygen content is 0.050% by mass or more. The above evaluation results are shown in Tables 4 to 6.

[0095] [Table 4]

[0096] [Table 5]

[0097] [Table 6]

[0098] As shown in Tables 4 to 6, the martensitic stainless steel sintered body obtained using the metal powder of the Examples had a sufficiently high relative density and a high mechanical strength compared to the sintered body obtained using the metal powder of the Comparative Examples. Therefore, it was confirmed that the present invention makes it possible to manufacture a high-density sintered body by powder metallurgy without carrying out a densification treatment such as HIP treatment. [Explanation of symbols]

[0099] S102: composition preparation step, S104: molding step, S106: degreasing step, S108: sintering step

Claims

1. Contains C in an amount of 0.42 mass% or more and 0.70 mass% or less, Contains 12.0% by mass or more and 14.0% by mass or less of Cr, Contains Nb in an amount of 1.2 mass% or more and 2.7 mass% or less, The Si content is 0.65 mass% or more and 1.0 mass% or less, The Mn content is 0.71 mass% or more and 1.0 mass% or less, The Ni content is 0.07 mass% or more and 0.60 mass% or less, The balance is Fe and impurities contained in an amount of 0.05% by mass or less, A martensitic stainless steel powder characterized in that, when an average particle size D50 is defined as the particle size at which the cumulative amount is 50% from the small diameter side in a cumulative particle size distribution on a mass basis obtained by a laser diffraction method, the average particle size D50 is 10 μm or less.

2. Contains C in an amount of 0.40% by mass or more and 0.70% by mass or less, Contains 12.0% by mass or more and 14.0% by mass or less of Cr, Contains Nb in an amount of 1.2 mass% or more and 2.7 mass% or less, The Si content is 0.65 mass% or more and 1.0 mass% or less, The Mn content is 0.71 mass% or more and 1.0 mass% or less, The Ni content is 0.07 mass% or more and 0.60 mass% or less, The balance is Fe and impurities contained in an amount of 0.05% by mass or less, A martensitic stainless steel sintered body having a relative density of 99.0% or more.

Citation Information

Patent Citations

  • Ferrous sintered alloy and its production

    JP1994279959A

  • Method and apparatus for injection molding of slurry

    JP1995166208A

  • stainless steel alloy

    JP2013541633A

  • Mixed powder for powder metallurgy, sintered compact, and method for producing sintered compact

    WO2017047100A1